ENTREPRENEURSHIP AS A SOURCE OF TECHNOLOGICAL CHANGES - Klymenchukova, Nataliia (Collection of scientific papers «ΛΌГOΣ», 2022)
Effective business can also be considered a source of technological change and the key to ensuring the competitiveness of the national economy. At the same time, such activities should be based on the philosophy of "kaizen", ie focus on continuous product improvement, production technology, marketing tools and labor organization, which in the long run should lead to profit and satisfaction of the general population. An important role in ensuring the effective development of knowledge-based entrepreneurship is played by the ability to adapt and diversify production, taking into account available resources, especially knowledge. In this case, access to new knowledge through the use of the process of assimilation of existing technologies through both market and non-market channels is not as time-consuming and capital-intensive process as generating knowledge as a result of personal research and development by the entrepreneur personally. This is based on the fact that the research activities of entrepreneurs are associated with a high level of risk, which can lead to bankruptcy [1-19]. The emergence of innovations in entrepreneurship and their dissemination is based on the transfer of technology and only together (innovation and technology) form a set of phenomena characteristic of scientific and technological progress in the innovation economy. Knowledge in the innovative economy, acquired by the entrepreneur - is a specific type of good with its inherent characteristics [20-22]. On the one hand, it is a public good available in the form of research, articles, reports, and on the other hand, it can be traded on the market. In this case, knowledge in an innovative economy is considered by the entrepreneur as information or goods that need protection under intellectual property rights. Knowledge in an innovative economy covers almost everything that surrounds a person [23-27]. Diffusion of technologies and knowledge is purely technical in nature, as it does not guarantee its effective assimilation by enterprises. Fundamental in this process is the presence of skills in the entrepreneur to master technologies, create new ones, as well as modification and adaptation of technological capabilities or industrial facilities to the use of capital goods. Effective technology transfer and assimilation should include an extensive range of resources for entrepreneurs, not only technical but also organizational skills, experience in marketing, management or finance.